Role of Anemia and Leukocytosis as Severity Predictors of Coronary Artery Disease Stenosis : A Retrospective Cross-sectional Study - M Saugi Abduh; Muhammad Rizki Triono; Retno Widyastuti (Universitas Wijaya Kusuma Surabaya, 2024)
Background: Anemia and leukocytosis were found to be associated with conditions that higher the risk for the formation of atherosclerotic plaque which will develop into cardiovascular disease. Basic laboratory parameters such as anemia and leukocytosis are not routinely used to assess Coronary Artery Disease (CAD) severity based on its stenosis. This study aimed to analyze the role of simple laboratory examiantion anemia and leukocytosis as predictors of the severity of stenosis in CAD. Methods: Cross-sectional approach was used in this study. Secondary data on CAD patients treated at Sultan Agung Islamic Hospital Semarang in 2022 were analyzed. Anemia and leukocytosis are the main risk factors analyzed in this study. Other risk factors such as gender, age, smoking status, hypertension and diabetes mellitus (DM) were also included in the analysis of this study. We performed bivariate analysis and multivariate analysis to see the relationship between these risk factors and the CAD stenosis severity. Results: Bivariate analysis with chi-square showed that anemia had a significant relationship with CAD severity (P<0.05). Multivariate analysis between anemia and smoking status reported that anemia was the most significant risk factor for the CAD stenosis severity (P<0.05). Conclusion: No association found between leukocytosis and CAD severity.